Production method of porous spherical silica gel particles
The porous spherical silica particles formed by the emulsion method solve the problem of difficulty in controlling the pore volume and surface area in the prior art, and achieve efficient production of particles with high surface area and pore volume, which is suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202380040930.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-15
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to produce spherical single-particle gel porous silica particles with both high pore volume and high surface area, and it is difficult to reliably control particle size, pore size and pore volume.
The alkali metal silicate is mixed with inorganic acid to form a silica sol through the emulsion method and mixed with oil and surfactant to form a water-in-oil emulsion. The pH of the emulsion is adjusted to control the gelation process and pore structure to form a high surface area and pore volume porous spherical silica particles.
It has achieved the production of porous spherical silica particles with high surface area and pore volume. It is suitable for catalysts, chromatographic media and other applications, and has a narrow particle size distribution, which is suitable for a variety of industrial uses.
Smart Images

Figure BDA0005136971570000071 
Figure BDA0005136971570000081 
Figure BDA0005136971570000082
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority to U.S. Provisional Application No. 63 / 320,600, filed on March 16, 2022, the contents of which are incorporated herein by reference in their entirety. Background Art
[0003] Porous spherical silica particles are widely used. For example, they can be used as fillers for films and resins, carriers or supports for various catalysts, fillers for cosmetics, filling materials for chromatography, desiccants, and for other purposes. The requirements for the physical properties of silica particles (e.g., particle size, particle shape, particle size distribution, pore size, pore volume, and surface area) may vary depending on the application.
[0004] A variety of methods for producing porous spherical silica particles are known in the art. For example, in some methods, an aqueous sodium silicate solution or an alkyl silicate is emulsified in a solvent and then gelled. In other methods, an aqueous sodium silicate solution or an alkyl silicate is gelled and then emulsified and granulated in a solvent. In addition, in other methods, a silica sol or an alkali silicate is spray dried to form porous spherical particles. In addition, some methods involve wet grinding of a hydrogel and then spray drying. However, there is still a need for a simple, economical method for producing porous spherical silica particles in which pore size, pore volume and particle size can be reliably controlled. Summary of the invention
[0005] The invention provides a method for forming a porous spherical silica material, which comprises mixing an alkali metal silicate with an inorganic acid to form a silica sol, mixing the silica sol with oil and a surfactant to form an emulsion, adding an alkaline solution to the emulsion to form a gel, adding a demulsifier, and filtering to obtain silica gel particles.
[0006] The silica material formed by the method can include a plurality of porous spherical silica gel particles. Each particle can include a rigid network of amorphous silica. The particles can have an average aspect ratio of about 1.2 or less, an average pore volume greater than about 0.3 cc / g, and at least about 200 m 2 Average surface area of 1 μm / g; median particle size of about 1 μm or larger.
[0007] Other features and other aspects of the disclosure are discussed in more detail below. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 A process flow chart of the production method according to the present disclosure is shown.
[0009] Figure 2 An SEM image of the silica particles produced in Example 1 is shown.
[0010] Figure 3 An SEM image of the silica particles produced in Example 2 is shown.
[0011] Figure 4 An SEM image of the silica particles produced in Example 3 is shown.
[0012] Figure 5 An SEM image of the silica particles produced in Example 4 is shown.
[0013] Figure 6 An SEM image of the silica particles produced in Example 5 is shown.
[0014] Figure 7 An SEM image of the silica particles produced in Example 6 is shown.
[0015] Figure 8 An SEM image of the silica particles produced in Example 7 is shown.
[0016] Fig. 9 An SEM image of the silica particles produced in Example 8 is shown.
[0017] Fig.10 An SEM image of the silica particles produced in Example 9 is shown. DETAILED DESCRIPTION
[0018] Before describing several exemplary embodiments, it is to be understood that the invention is not limited to the details of construction or method steps set forth in the following description. The invention is capable of other embodiments and of being practiced or carried out in various ways.
[0019] The embodiments exemplarily described herein may be appropriately implemented in the absence of any one or more elements, one or more limitations not specifically disclosed herein. Therefore, for example, the terms "comprise", "include", "contain", etc. should be widely understood and unrestricted. In addition, the terms and expressions used herein have been used as descriptive terms rather than limiting terms, and the use of such terms and expressions is not intended to exclude any equivalents of the features shown and described or parts thereof, but it should be recognized that various modifications can be made within the scope of the claimed technology. In addition, the phrase "essentially consisting of..." should be understood to include those elements specifically enumerated and those additional elements that will not have a substantial impact on the basic features and novel features of the claimed technology. The phrase "consisting of..." excludes any unspecified elements.
[0020] As used herein, "about" will be understood by one of ordinary skill in the art and will vary to some extent depending on the context in which it is used. If the use of a term is unclear to one of ordinary skill in the art, "about" will mean up to plus or minus 10% of the particular term, taking into account the context in which it is used.
[0021] The use of the terms "a," "an," and "the" and similar referents in the context of describing elements (especially in the context of the following claims) are to be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context.
[0022] Those skilled in the art will appreciate that, for any and all purposes, particularly in providing a written description, all ranges disclosed herein also encompass any and all possible subranges and combinations of subranges thereof. Any listed range can be easily understood to fully describe and be able to decompose the same range into at least equal halves, thirds, quarters, fifths, tenths, etc. As a non-limiting example, each range discussed herein can be easily decomposed into a lower third, a middle third, and an upper third, etc. Those skilled in the art will also appreciate that all language, such as "at most," "at least," "greater than," "less than," etc., includes the numbers listed and refers to a range that can be subsequently decomposed into subranges as discussed above. Finally, those skilled in the art will appreciate that a range includes each individual member.
[0023] In general, the present disclosure relates to a method for forming a single-particle (single) gel porous silica particle by an emulsion method. The method generally includes preparing a silica sol by mixing an alkali metal silicate with an acid at a specific pH and temperature, and then mixing the sol with an oil and a surfactant to produce an oil-in-water emulsion. The term "oil-in-water emulsion" is used herein to represent an emulsion in which oil is a continuous phase and water is a dispersed phase. It should be understood that the "water" used in the term "oil-in-water emulsion" includes aqueous silica sol. The pH can then be adjusted by adding an alkaline compound to the emulsion to control the gelation process and the final pore structure within the emulsion. It was found that the particle size, particle size distribution, pore volume, pore size and surface area can be reliably controlled by manipulating certain aspects of the emulsion method. In addition, the method forms spherical single-particle gel particles, which show various advantages over particles formed by conventional methods (such as those formed by spray drying agglomeration methods).
[0024] For example, if used as a catalyst support, catalysts containing single-particle gel support particles tend to perform better in olefin polymerization processes than catalysts containing agglomerated support particles. As used herein, single-particle gel particles refer to particles that are not formed by agglomerates of smaller particles. Agglomerates refer to the product of a combination of particles held together by various physical-chemical forces. More specifically, agglomerates are composed of multiple adjacent component primary particles that are bonded and connected at their contact points. Unlike agglomerates, single-particle gel particles cannot be separated into smaller particles without breaking the particles.
[0025] The method is also suitable for forming gel particles for a variety of applications, including, for example, as catalyst supports, chromatography media, plastic additives, personal care and cosmetics, as the method is able to produce particles with desired particle size and pore properties.
[0026] This method can be used to form particles having a relatively high surface area, as measured by the BET method using nitrogen adsorption as described below. For example, the average surface area of the particles can be about 200 m 2 / g or greater, in some embodiments about 300m 2 / g or greater, in some embodiments about 400m 2 / g or greater, in some embodiments about 500m 2 / g or greater, in some embodiments about 600m 2 / g or greater, in some embodiments about 700m 2 / g or more. The average surface area of the particles can be about 1000m 2 / g or less, in some embodiments about 900m 2 / g or less, in some embodiments about 800m 2 / g or less, in some embodiments about 700m 2 / g or less, in some embodiments about 500m 2 / g or less.
[0027] In addition, the method can be used to form particles with relatively high pore volumes, as measured by nitrogen pore volume as described below. For example, the average pore volume of the particles can be about 0.3cc / g or greater, in some embodiments about 0.5cc / g or greater, in some embodiments about 0.8cc / g or greater, in some embodiments about 1.2cc / g or greater. The pore volume can be about 2.5cc / g or less, in some embodiments about 2.0cc / g or less, in some embodiments about 1.5cc / g or less, in some embodiments about 1cc / g or less. In some embodiments, the pore volume ranges from 0.3cc / g to 2.5cc / g, in some embodiments about 0.5cc / g to 2cc / g, and in some embodiments about 0.8cc / g to about 1.5cc / g.
[0028] The method can produce particles having an average pore size of about 30 angstroms or greater, in some embodiments, about 50 angstroms or greater, in some embodiments, about 70 angstroms or greater, in some embodiments, about 100 angstroms or greater, in some embodiments, about 150 angstroms or greater, as measured by nitrogen porosimetry. The average pore size can be about 300 angstroms or less, in some embodiments, about 250 angstroms or less, and in some embodiments, about 200 angstroms or less.
[0029] The surface area was determined by BET nitrogen adsorption analysis after the sample was activated under vacuum for 30 minutes at 400°C. The surface area was calculated from multiple point values of nitrogen volume absorption during the adsorption branch at low [P / Po = ~0.05 to 0.15] partial pressures. The adsorption branch of the isotherm stopped at a partial pressure of P / Po = 0.995, and the descending branch of the isotherm was then measured. The nitrogen pore volume was calculated by applying the Gurvich rule at P / Po = 0.995. The pore size is reported as the calculated BJH desorption average diameter.
[0030] In the past, it has been difficult to produce spherical single-particle gel porous silica particles having both high pore volume and high surface area. However, in some embodiments, the methods described herein can produce spherical single-particle gel porous silica particles having an average pore volume of about 2.3 cc / g or greater and an average surface area of greater than about 350 m 2 When used in catalyst applications, for example, such a combination allows for high catalyst loading on the support and high catalytic activity in the polymerization process.
[0031] The method can produce porous silica particles having a median particle size (D50) of about 1 μm or greater, in some embodiments about 3 μm or greater, in some embodiments about 8 μm or greater, in some embodiments about 15 μm or greater, and in some embodiments about 20 μm or greater as measured by laser diffraction as described below. The average particle size can be about 50 μm or less, in some embodiments about 40 μm or less.
[0032] Regardless of their average size, this process can produce particles with a relatively narrow size distribution. The width of the particle size distribution can be measured as the distribution span, which is defined by the following equation: Where D 10 , D 50 and D 90 They represent the 10th, 50th and 90th percentiles of the particle size (diameter) distribution, i.e., D 90 This means that 90% by volume of the particles have a diameter less than or equal to 100 microns. In this regard, the distribution span of the particles can be about 2.0 or less, in some embodiments about 1.5 or less, in some embodiments about 1.45 or less, in some embodiments about 1.4 or less, in some embodiments about 1.3 or less, and in some embodiments from about 0.9 to about 1.25.
[0033] The inventors unexpectedly discovered that the emulsion process described herein can produce porous silica particles having the above-mentioned unique properties. In addition, it has been discovered that the particle size, particle size distribution, pore size, pore volume and surface area of the particles can be controlled by manipulating certain aspects of the emulsion process.
[0034] In the water-in-oil emulsion method, silica sol is prepared by mixing an alkali metal silicate with an acid. The sol is then mixed with oil and a surfactant to form an emulsion. In the emulsion formed in this process, the oil phase is continuous and the sol forms stable spherical droplets dispersed in the oil phase. The pH can then be adjusted by adding an alkaline compound to the emulsion, which can help control the gelation process and the final pore structure in the emulsion.
[0035] refer to Figure 1The method is described in more detail. First, in step 101, silica sol is formed by mixing an inorganic acid and an alkali metal silicate. The alkali metal silicate may include sodium silicate, potassium silicate, lithium silicate, etc. The alkali metal silicate is generally provided in an aqueous solution at a concentration of about 5 wt % to about 50 wt % (based on SiO2 in the alkali metal silicate), for example, about 10 wt % to about 35 wt %. The inorganic acid may be sulfuric acid, hydrochloric acid, nitric acid, etc. In some embodiments, the alkali metal silicate is sodium silicate, and the inorganic acid is sulfuric acid. In other embodiments, the alkali metal silicate is sodium silicate, and the inorganic acid is hydrochloric acid. In order to form a sol, the alkali metal silicate may be added to a container containing an inorganic acid. The flow rate is adjusted to obtain the desired output of an industrial scale. For example, at a laboratory scale, the alkali metal silicate may be added to the inorganic acid at a flow rate of about 1 ml / min to about 250 ml / min, for example, about 5 ml / min to about 200 ml / min, preferably about 50 ml / min to about 200 ml / min. Alternatively, the alkali metal silicate and the inorganic acid can be mixed at once by pouring one into the other. The concentration of the inorganic acid is generally from about 10% by weight to about 50% by weight, in some embodiments from about 15% by weight to about 40% by weight, and in some embodiments from about 18% by weight to about 35% by weight. The weight ratio of the inorganic acid to the alkali metal silicate preferably results in a pH of less than 7. The weight ratio of the inorganic acid to the alkali metal silicate is generally from about 1:10 to about 2:1, in some embodiments from about 1:7 to about 1:1, and in some embodiments from about 1:5 to about 1:2.
[0036] In some embodiments, the concentration and amount of aqueous alkali metal silicate and inorganic acid are selected to achieve a specified pH value. For example, in some embodiments, the pH of the resulting mixture is controlled to remain below about 4, such as below about 3, such as below about 1.5. The pH of the resulting mixture is typically about 1 or greater.
[0037] During the sol formation step, the temperature should be controlled at a relatively low temperature. For example, in some embodiments, the temperature is controlled at about 40°C or lower, in some embodiments, about 30°C or lower, and in some embodiments, about 20°C or lower.
[0038] In order to form colloidal sol, a mixer (e.g., an overhead mixer) can be used to continuously mix mineral acid and alkali metal silicate in a container. The mixer can be enough to form the time period of colloidal sol with any suitable speed operation. For example, in some embodiments, the mixture can be mixed for about 2 minutes to about 1 hour, for example, about 5 minutes to about 45 minutes, for example, about 10 minutes to about 40 minutes.
[0039] After forming colloidal sol, in step 102, it is pumped into or otherwise mixed with oil and surfactant to form water-in-oil emulsion. Oil and surfactant can be mixed to form surfactant / oil mixture, and the mixture is added to colloidal sol. The amount of surfactant can be controlled to form stable spherical silica sol droplets. In some embodiments, the amount of surfactant in the mixture is about 3 weight % to about 25 weight % of total surfactant / oil mixture. Preferably, the amount of surfactant in the mixture is about 5 weight % to about 15 weight %. Alternatively, oil and surfactant are added to the colloidal sol respectively in an amount sufficient to provide the surfactant / oil mixture with the above-mentioned weight percentage.
[0040] The oil is not particularly limited except that it should be non-reactive and immiscible with aqueous alkali metal silicates and inorganic acids. Exemplary oils include n-octane, gasoline, kerosene, isoparaffin oils, etc., alicyclic hydrocarbons such as cyclononane, cyclodecane, etc., aromatic hydrocarbons such as toluene, xylene, ethylbenzene, tetralin, etc., and alkane mixtures such as mineral oil.
[0041] A wide range of surfactants can be used including: caprylic acid glyceryl, monolauric acid glyceryl, mono / dicocoic acid glyceryl, dilauric acid glyceryl, monostearate glyceryl, distilled monostearate glyceryl, distearate glyceryl, monooleate glyceryl, dioleate glyceryl, trioleate glyceryl, monoisostearate glyceryl, monoricinoleate glyceryl, monohydroxystearate glyceryl, POE monostearate glyceryl, acetylated monostearate glyceryl, succinylated monostearate glyceryl, diethyl Acylated tartaric acid monostearate, modified phthalic acid glyceryl resin, monostearate triglyceride, monooleate triglyceride, monoisostearate triglyceride, tetraoleate decaglycerol, decaglycerol decaglycerol, pentaerythritol monolaurate, monostearate pentaerythritol, distearate pentaerythritol, tetrastearate pentaerythritol, monooleate pentaerythritol, dioleate pentaerythritol, trioleate pentaerythritol, tetraricinoleate pentaerythritol, monolaurate sorbitan ester, POE monolaurate Sorbitan cinnamate, sorbitan monopalmitate, POE sorbitan monopalmitate, sorbitan monostearate, POE sorbitan monostearate, sorbitan tristearate, POE sorbitan tristearate, sorbitan monooleate, POE sorbitan monooleate, sorbitan sesquioleate, sorbitan trioleate, POE sorbitan trioleate, POE sorbitan trioleate, POE sorbitan hexaoleate, POE sorbitan laurate oleate, POE sorbitan polyoleate Esters, POE sorbitol, beeswax esters, sucrose monolaurate, sucrose cocoate, sucrose monomyristate, sucrose monopalmitate, sucrose dipalmitate, sucrose monostearate, sucrose distearate, sucrose monooleate, sucrose dioleate, lauryl lactate, cetyl lactate, sodium lauryl lactylate, sodium stearoyl lactylate, sodium isostearyl-2-lactylate, sodium stearoyl-2-lactylate, calcium stearoyl-2-lactylate, sodium capryl lactate, lauryl alcohol, and cetyl alcohol.
[0042] In one embodiment, the surfactant comprises at least one sorbitan ester. Sorbitan esters include sorbitan fatty acid esters, wherein the fatty acid component of the ester includes a carboxylic acid having from about 10 to about 100 carbon atoms, and in one embodiment, from about 12 to about 24 carbon atoms. Sorbitan is a mixture of sorbitans, primarily 1,4-sorbitan and isosorbide (Formulas I and II):
[0043]
[0044]
[0045] Sorbitol anhydride (also referred to as monoanhydrosorbitol or sorbitan) is the common name for anhydrides derived from sorbitol by removing a water molecule. Sorbitol anhydride fatty acid esters of the present invention are mixtures of partial esters of sorbitol and its anhydride with fatty acids. These sorbitol anhydride esters can be represented by the following structure, which can be any one of monoesters, diesters, triesters, tetraesters or their mixtures (Formula III):
[0046]
[0047] In formula (III), each Z independently represents a hydrogen atom or C(O)R-, and each R independently represents a hydrocarbon group of about 9 to about 99 carbon atoms, more preferably about 11 to about 23 carbon atoms. Examples of sorbitan esters include sorbitan stearate and sorbitan oleate, such as sorbitan stearate (i.e., monostearate), sorbitan distearate, sorbitan tristearate, sorbitan monooleate, and sorbitan sesquioleate. Sorbitol esters also include polyoxyalkylene sorbitan esters, wherein the alkylene group has about 2 to about 30 carbon atoms. These polyoxyalkylene sorbitan esters can be represented by formula IV:
[0048]
[0049] wherein in Formula IV, each R is independently an alkylene group of from about 2 to about 30 carbon atoms; R' is a hydrocarbyl group of from about 9 to about 99 carbon atoms, more preferably from about 11 to about 23 carbon atoms; and w, x, y, and z represent the number of repeating oxyalkylene units. For example, ethoxylation of sorbitan fatty acid esters produces a series of more hydrophilic surfactants as a result of the reaction of the hydroxyl groups of sorbitan with ethylene oxide. A major class of these ethoxylated sorbitan esters are those containing from about 2 to about 80 ethylene oxide units, and in one embodiment from about 2 to about 30 ethylene oxide units, and in one embodiment about 4, in one embodiment about 5, and in one embodiment about 20 ethylene oxide units. Typical examples are polyoxyethylene (hereinafter referred to as "POE") (20) sorbitan tristearate, POE (4) sorbitan monostearate, POE (20) sorbitan trioleate, POE (5) sorbitan monooleate and POE (80) sorbitan monooleate. As used herein, the numbers in brackets refer to the number of ethylene oxide units present in the composition.
[0050] Useful surfactants of the types listed above can be generally represented by the following classes of chemical compounds, members of which are commercially available and suitable provided that their use in accordance with the teachings herein enables the production of stable emulsions:
[0051] (a) sorbitol esters, the general formula of which is
[0052]
[0053] Wherein: the groups X are identical or different from each other and are each OH or R 1 COO - ;
[0054] Where R 1 is a linear or branched, saturated or unsaturated aliphatic hydrocarbon group, which is optionally substituted by a hydroxyl group and has 7 to 22 carbon atoms, provided that at least one of the groups X is R 1 COO - ,
[0055] (b) fatty acid esters, the general formula of which is:
[0056]
[0057] Where: R 2 is a linear or branched, saturated or unsaturated aliphatic hydrocarbon group, which is optionally substituted by a hydroxyl group and has 7 to 22 carbon atoms;
[0058] R 3 A straight or branched C1-C 10 Alkylene;
[0059] n is an integer greater than or equal to 6; and
[0060] R 4 H, straight or branched C1-C 10 Alkyl or
[0061]
[0062] Where R 5 As mentioned above, R 2 as defined; and
[0063] (c) polyalkoxylated alkylphenol, the general formula of which is
[0064]
[0065] Where: R 6 A straight or branched C1-C 20 alkyl;
[0066] m is an integer greater than or equal to 8; and
[0067] R 7 and R 8 As described above for R of formula (II), 3 and R 4 As defined.
[0068] Typically, the weight ratio of the sol to the oil and surfactant mixture can be from about 1:5 to about 5:1, such as from about 1:4 to about 4:1, such as from about 1:3 to about 2:1, such as from about 1:2 to about 2: 1. In some embodiments, the oil is mineral oil and the surfactant is a sorbitan ester, such as sorbitan monooleate, and the weight ratio ranges from 1:2 to 2:1.
[0069] To obtain the desired silica sol droplet size, the temperature can be controlled during the emulsion formation step. For example, the temperature can be maintained above about 30°C, such as about 40°C to about 80°C, such as about 50°C to about 65°C, when forming the emulsion.
[0070] The mixing speed should be high enough to form a stable emulsion, i.e., an emulsion that does not separate when left at room temperature for the desired period of time, and to obtain the desired silica sol droplet size. Such mixing speeds can be achieved using an overhead mixer (e.g., mixer) or in-line mixer (e.g. Mixer) to achieve. After the sol is pumped into the reaction vessel completely or otherwise fully mixed, the emulsion can be continuously mixed for a period of time that is enough to keep a stable emulsion. For example, in some embodiments, mixing can last for a period of time from about 1 minute to about 1 hour.
[0071] After forming the emulsion, the method proceeds to step 103, wherein the pH of the emulsion is optionally adjusted. Alkaline compounds can be used to adjust the pH. For example, in various embodiments described herein, any known or later found alkali can be used to adjust the pH. In various embodiments, the alkali can be selected from NaOH, ammonia, ammonium hydroxide (e.g., NH4OH), KOH, Na2CO3, TMAOH, NaAlO2, and mixtures thereof. In addition, the alkali used can be in the form of a solution with a concentration range of 0.2% to 50%. In various embodiments, the above-mentioned alkali can have a pH of at least 7, such as about 8 to about 14, such as about 9 to about 13. The amount of the alkaline compound used is determined by the target pH to be reached. For example, in some embodiments, alkaline compounds are added until the pH reaches about 3 or more, about 4 or more in some embodiments, about 5 or more in some embodiments, about 6 or more in some embodiments, about 7 or more in some embodiments, and about 8 or more in some embodiments. The pH usually reaches about 12 or less, about 11 or less in some embodiments, about 10 or less in some embodiments, and about 9 or less in some embodiments. For example, in some embodiments, ammonium hydroxide is added until the pH reaches about 3 to about 10, such as about 5 to about 9. The emulsion can be mixed continuously while the alkaline compound is added, and for a short period of time thereafter to promote pH stabilization. The mixing speed can optionally be reduced at this stage. For example, in some embodiments, the mixing speed is reduced to a speed of about 10% to about 60% of the mixing speed used to form the emulsion.
[0072] It should be understood that the pH does not necessarily need to be adjusted, and step 103 is optional. The pore characteristics of the resulting silica particles can be controlled by adjusting the pH of the emulsion during the gelation process. Therefore, the pH should be adjusted to the level required to obtain the desired pore characteristics. Therefore, in some cases, it is not necessary to adjust the pH at all.
[0073] After the optional pH adjustment step, the method can proceed to step 104, wherein the silica is gelled. The gelling process can include optionally adding water to the emulsion and raising the temperature, while optionally continuously mixing. The volume of water added at this stage is not critical, but can be about 0.25 times to about 10 times the volume of the mixture in the container. In other embodiments, no water is added.
[0074] The gelation temperature may range from about 50° C. to about 95° C., in some embodiments from about 70° C. to about 90° C., and in some embodiments from about 75° C. to about 85° C. The mixing speed may be maintained at a speed similar to that in step 103. The temperature and mixing speed may be maintained for a time sufficient to allow the silica to gel. For example, in some embodiments, the gelation time may be from about 20 minutes to about 2 hours, such as from about 30 minutes to about 90 minutes.
[0075] In some embodiments, the silica gel obtained can be aged before separation. In this case, the silica gel obtained is maintained at a temperature of about 50°C to about 95°C, in some embodiments about 70°C to about 90°C, in some embodiments about 75°C to about 85°C, for a period of about 10 minutes to about 10 hours, in some embodiments about 30 minutes to about 5 hours, and in some embodiments about 45 minutes to about 2 hours. The pH can be optionally adjusted during the aging process. In this way, the surface area and pore size can be adjusted in situ, and the gel network can be enhanced.
[0076] After the gelling step, the method can proceed to the separation in step 105. Any suitable method can be used to separate the solid silica gel particles from the oil phase and the water phase of the mixture. For example, in some embodiments, mixing is stopped so that the oil and surfactant are separated from the formed silica particles. In some embodiments, solid particles can be filtered out from the mixture.
[0077] The resulting silica particles may then be optionally washed in step 106, for example by stirring them in an acid, water, and / or alcohol. The particles may then be dried using any suitable method in step 107. For example, in some embodiments, the particles may be dried at a temperature and time sufficient to remove the desired amount of moisture. In some embodiments, the particles may be dried in a vacuum oven at a temperature of about 40° C. to about 80° C. for about 30 minutes to about 24 hours. In some embodiments, the particles may be dried in a conventional oven at a temperature of about 90° C. to about 130° C. for about 30 minutes to about 24 hours. In some embodiments, a spray dryer may be used to dry the particles. In other embodiments, the particles may be dried by flash drying or by co-evaporation using an organic solvent.
[0078] In some embodiments, in order to facilitate the separation of oil and surfactant from the emulsion, the emulsion is demulsified by adding a demulsifier. In some embodiments, the demulsifier is water or acid, such as an inorganic acid. For example, in some embodiments, deionized water or an aqueous inorganic acid is added to the emulsion as a demulsifier. For example, when using an aqueous sulfuric acid composition as a demulsifier, the concentration of sulfuric acid can be about 1 weight % to about 30 weight % of the total aqueous composition, and in some embodiments about 5 weight % to about 15 weight %. The demulsifier can be added to the emulsion in a weight ratio of about 1:5 to about 5:1 relative to the weight of the emulsion, and in some embodiments, in a weight ratio of about 1:2 to about 1:1.
[0079] Demulsification can occur at high temperatures. For example, the temperature can be from about 50°C to about 95°C, from about 60°C to about 90°C in some embodiments, and from about 70°C to about 80°C in some embodiments. During demulsification, the mixture can optionally be stirred by any suitable means. For example, in some embodiments, after adding a demulsifier, the mixture is stirred at high temperatures for about 30 minutes to about 5 hours, for example, from about 1 hour to about 3 hours. In other embodiments, the mixture is kept at high temperatures without stirring for about 30 minutes to about 5 hours, for example, from about 1 hour to about 3 hours.
[0080] After demulsification, the particles can be separated from the rest of the mixture by any suitable means. For example, in some embodiments, the mixture can be transferred to a separatory funnel to separate the aqueous phase from the oil phase. The silica particles can then be separated from the rest of the liquid. In some embodiments, for example, the particles can be repeatedly filtered and redispersed as needed.
[0081] After separation, optionally Figure 1 The particles are aged as shown in step 106a. The particles can be aged at high temperature in an ammonia solution. In some embodiments, the particles are redispersed in an aqueous medium, heated and mixed with ammonium hydroxide for an appropriate period of time. The pH of the redispersed particles in the aqueous medium can be from about 1 to about 5, for example, from about 2 to about 4. The aging temperature can be from about 50°C to about 95°C, in some embodiments from about 70°C to about 90°C, and in some embodiments from about 75°C to about 85°C. Ammonium hydroxide can be added until the pH of the solution reaches about 6 to about 9, for example, from about 7 to about 8. In some embodiments, the particles are aged for a period of about 10 minutes to about 10 hours, in some embodiments from about 30 minutes to about 5 hours, and in some embodiments from about 45 minutes to about 2 hours.
[0082] If the particles are aged in such a solution, they can then be filtered and dried. For example, in some embodiments, the particles can be filtered out of the ammonia solution, redispersed in water as needed, and then filtered and dried to remove water and any solvent to form a powder. In some embodiments, after filtering from the ammonia solution, the particles are redispersed in deionized water and then dried at high temperature for a suitable period of time. Any suitable temperature can be used to dry the particles. In some embodiments, for example, the particles are dried at a temperature of about 50°C to about 250°C, in some embodiments about 80°C to about 200°C, and in some embodiments about 100°C to about 150°C, for a period of about 1 hour to about 48 hours, for example, about 5 hours to about 24 hours, although time and temperature are not critical.
[0083] Emulsion methods for forming porous silica particles can provide additional advantages over conventional methods. For example, in conventional methods for producing porous silica gel particles having a desired particle size, a grinding step is typically employed. This grinding step tends to produce very small silica particles, referred to as "fines." However, advantageously, the methods disclosed herein produce particles having a desired particle size and do not require grinding.
[0084] During the above-mentioned method, silica gel particles are formed in droplets of emulsion to provide porous spherical silica particles. Each particle contains a rigid network of amorphous silica. Therefore, the particles tend to be highly spherical. One method of measuring the sphericity of particles is to take images of multiple particles and calculate the aspect ratio of each particle using the maximum diameter and minimum diameter of each particle that can be determined from the image. Then, the average aspect ratio of the particles can be calculated using the aspect ratio of a single particle. The aspect ratio is an indicator of sphericity. Particles with low aspect ratios are more spherical than particles with high aspect ratios. In this regard, the particles formed by any of the above-mentioned methods are highly spherical and can have a low average aspect ratio, such as about 1.2 or less, about 1.17 or less in some embodiments, about 1.15 or less in some embodiments, about 1.12 or less in some embodiments, and about 1.1 or less in some embodiments. For example, in some embodiments, at least 75% of the particles have an aspect ratio of about 1.2 or less, such as about 1.1 or less. In some embodiments, at least 50% of the particles have an aspect ratio of about 1.1 or less. The aspect ratio is typically about 1.0 or greater.
[0085] As described above, porous silica particles with high sphericity can be used in a variety of applications. For example, silica particles can be used as catalyst carriers, insulating materials, toners, food additives, medical diagnostic agents, coating fillers, cosmetic fillers, resin fillers, chromatographic media, adsorbents, desiccants, etc.
[0086] The present disclosure may be better understood with reference to the following examples.
[0087] Example
[0088] Test method:
[0089] Surface area, pore volume and average pore size were measured by nitrogen adsorption. The instrument used for the analysis was an autosorb iQ2 TPX from Quantachrome Instrument. The nitrogen adsorption method is known as BET and is described in S. Brunauer, PH Emmett and E. Teller, J. Am. Chem. Soc., 1938, 60, 309.
[0090] Prior to analysis, the samples were vacuum activated at 400°C for 30 minutes. The surface area was calculated from multiple points of nitrogen volume uptake during the adsorption branch at low [P / Po = ~0.05 to 0.15] partial pressures. The adsorption branch of the isotherm was stopped at a partial pressure of P / Po = 0.995, and the descending branch of the isotherm was then measured. The pore volume was calculated by applying the Gurvich rule at P / Po = 0.995. The pore size is reported as the calculated BJH desorption average diameter.
[0091] The silica gels of the present invention are typical mesoporous materials (pore size 2-50 nm, IUPAC definition), and they generally show type IV isotherms (IUPAC classification). Therefore, nitrogen porosimetry is a suitable method for characterizing them, and the determination of surface area using the BET method and the determination of pore volume from nitrogen adsorption and desorption isotherms using the BJH method are well-established and suitable methods and are used herein.
[0092] After 2 minutes of ultrasonic treatment, the average particle size (D50) and the particle size distribution were measured using a Malvern 3000 particle size analyzer apparatus from Brightwell Technologies Inc. The refractive index used for the measurements was 1.49.
[0093] The aspect ratio was determined from the SEM micrographs using Image-Pro Premier software. For each particle in the sample image, the aspect ratio was calculated by dividing the longest diameter by the shortest diameter. The aspect ratios of the individual particles of each sample were then averaged to determine the average aspect ratio of the particles in the sample. For each sample for which an aspect ratio was provided, approximately 150 particles were used for the calculation.
[0094] Example 1
[0095] The porous spherical silica material was obtained using an emulsion method. First, sodium silicate and an inorganic acid were reacted to prepare a sol. 2829 g of sodium silicate (14 wt %) was added to 850 g of an acid (25 wt % H2SO4) at a flow rate of 150 ml / min and the sol was stirred for 1 h. The sol was prepared at 15°C and a pH of 1.5 by mixing with an overhead mixer at 500 rpm for 10 minutes. 3500 g of the sol was mixed with mineral oil (3500 g) and a surfactant (sorbitan monooleate, 245 g). The mixture was continuously passed through a 1500 rpm column at a flow rate of 3.5 L / min. The emulsion was prepared by mixing with a pipeline mixer for 1 minute. The pH was adjusted to 5.5 by adding ammonium hydroxide to the emulsion to control the gelation process. The temperature was then raised to 60°C and aged at 60°C for 1 hour. 3000g of 5 wt% sulfuric acid was then added to demulsify the mixture at 60°C at 250rpm for 1 hour. After demulsification, the mixture was cooled to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected, and the silica particles were filtered out from the aqueous phase. The silica particles were repeatedly washed with 50°C water by re-slurrying the particles in water. This process was continued until the pH of the slurry reached 4. The particles were then subsequently dried with a spray dryer. The resulting particles were spherical porous silica having a D50 particle size of 20μm and a span of 1.4. The BET surface area of the resulting particles was 618m 2 / g, pore volume 1.4ml / g, average pore diameter about Figure 2 An image of the particles is shown. The average aspect ratio was 1.08. The properties of the resulting silica particles are summarized in Table 1 below.
[0096] Example 2
[0097] The porous spherical silica material was obtained using an emulsion method. First, sodium silicate and an inorganic acid were reacted to prepare a sol. 2869 g of sodium silicate (14 wt %) was added to 850 g of an acid (25 wt % H2SO4) at a flow rate of 200 ml / min and the sol was prepared using an emulsion method. The sol was prepared at 15°C and a pH of 1.5 by mixing with an overhead mixer at 500 rpm for 10 minutes. 3500 g of the sol was mixed with mineral oil (3500 g) and a surfactant (sorbitan monooleate, 245 g). The mixture was continuously passed through a 1250 rpm column at a flow rate of 3.5 L / min. The emulsion was prepared by mixing with a pipeline mixer for 1.5 minutes. The pH was adjusted to 6 by adding ammonium hydroxide to the emulsion to control the gelation process. The temperature was then raised to 60°C and aged at 60°C for 1 hour. 3000g of 5 wt% sulfuric acid was then added to demulsify the mixture at 60°C at 250rpm for 1 hour. After demulsification, the mixture was cooled to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected, and the silica particles were filtered out from the aqueous phase. The silica particles were repeatedly washed with 50°C water by re-slurrying the particles in water. The process was continued until the pH of the slurry reached 4. The particles were then subsequently dried with a spray dryer. The resulting particles were spherical porous silica having a D50 particle size of 35μm and a span of 1.5. The BET surface area of the resulting particles was 551m 2 / g, pore volume 1.3ml / g, average pore diameter about Figure 3 An image of the particles is shown. The average aspect ratio was 1.1. The properties of the resulting silica particles are summarized in Table 1 below.
[0098] Example 3
[0099] Use emulsion method to obtain porous spherical silica material. First, sodium silicate and inorganic acid are reacted to prepare sol. By adding 200g sodium silicate (14 wt %) to 53g acid (18.5% HCl) at a flow rate of 10ml / min, and using an overhead mixer to mix at 960rpm for 20 minutes, a sol is prepared at a temperature of 15°C and a pH of 1.5. The sol is then pumped into a mixture of mineral oil (300g) and a surfactant (sorbitan monooleate, 15g). An emulsion is prepared by continuously mixing the mixture at a speed of 960rpm at a temperature (60°C) for 10 minutes using an overhead mixer. The pH is adjusted to control the gelation process by adding 2.9g ammonium hydroxide to the emulsion. The emulsion is then mixed at 250rpm for 5 minutes. 400ml water is added to the emulsion. The temperature is then raised to 80°C. The emulsion is mixed at 250rpm for 1 hour to gel. After gelation, the mixture was cooled for 30 minutes to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected and the silica particles were filtered out from the aqueous phase. The silica particles were washed with 200 ml of water at pH 4 at 60°C while mixing at 250 rpm for 40 minutes and then filtered. The washing step was repeated twice more. The particles were then washed with isopropanol and subsequently dried in a vacuum oven at 60°C for 1 hour. The resulting particles were spherical porous silica with a D50 particle size of 14 μm and a span of 1.5. The BET surface area of the resulting particles was 456 m 2 / g, pore volume 1.5ml / g, average pore diameter about Figure 4Images of the particles are shown. The properties of the resulting silica particles are summarized in Table 1 below.
[0100] Example 4
[0101] Use emulsion method to obtain porous spherical silica material. First, sodium silicate and inorganic acid are reacted to prepare sol. By adding 253g sodium silicate (14 wt %) to 50.5g acid (18.5% HCl) at a flow rate of 10ml / min, using an overhead mixer to mix at 960rpm for 20 minutes, a sol is prepared at a temperature of 15°C and a pH of 1.5. The sol is then pumped into a mixture of oil (150g) and a surfactant (sorbitan monooleate, 10g). An emulsion is prepared by continuously mixing the mixture at a speed of 960rpm for 10 minutes at a stable temperature (60°C) using an overhead mixer. The pH is adjusted to control the gelation process by adding 2.4g ammonium hydroxide to the emulsion. The emulsion is then mixed at 250rpm for 5 minutes. 400ml water is added to the emulsion. The temperature is then raised to 80°C. The emulsion is mixed at 250rpm for 1 hour to gel. After gelation, the mixture was cooled for 30 minutes to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected and the silica particles were filtered out from the aqueous phase. The silica particles were washed with 200 ml of water at pH 4 at 60°C while mixing at 250 rpm for 40 minutes and then filtered. The washing step was repeated twice more. The particles were then washed with isopropanol and subsequently dried in a vacuum oven at 60°C for 1 hour. The resulting particles were spherical porous silica with a D50 particle size of 17 μm and a span of 1.3. The BET surface area of the resulting particles was 917 m 2 / g, pore volume 1.9ml / g, average pore diameter about Figure 5 Images of the particles are shown. The properties of the resulting silica particles are summarized in Table 1 below.
[0102] Example 5
[0103] Use emulsion method to obtain porous spherical silica material. First, sodium silicate and inorganic acid are reacted to prepare sol. By adding 201g sodium silicate (14 wt %) to 53.5g acid (18.5% HCl) at a flow rate of 10ml / min, and using an overhead mixer to mix at 960rpm for 20 minutes, a sol is prepared at a temperature of 15°C and a pH of 1.5. The sol is then pumped into a mixture of oil (91g) and a surfactant (sorbitan monooleate, 7.7g). The emulsion is prepared by continuously mixing the mixture at a speed of 960rpm for 10 minutes at a stable temperature (60°C) using an overhead mixer. The pH is adjusted to control the gelation process by adding 1.0g ammonium hydroxide to the emulsion. The emulsion is mixed for another 5 minutes at 250rpm. 400ml water is added to the emulsion. The temperature is then raised to 80°C. The emulsion is mixed at 250rpm for 1 hour to gel. After gelation, the mixture was cooled for 30 minutes to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected and the silica particles were filtered out from the aqueous phase. The silica particles were washed with 200 ml of water with a pH of 4 at 60°C while mixing at 250 rpm for 40 minutes and then filtered. The washing step was repeated twice more. The particles were then washed with isopropanol and subsequently dried in a vacuum oven at 60°C for 1 hour. The resulting particles were spherical porous silica with a D50 particle size of 9 μm and a span of 1.1. The BET surface area of the resulting particles was 505 m 2 / g, pore volume 2.5ml / g, average pore diameter about Figure 6 Images of the particles are shown. The properties of the resulting silica particles are summarized in Table 1 below.
[0104] Example 6
[0105] The porous spherical silica material was prepared using an emulsion method. First, sodium silicate and an inorganic acid were reacted to prepare a sol. 805 g of sodium silicate (22.5 wt %) was added to 455 g of an acid (25 wt % H2SO4) at a flow rate of 80 ml / min and the mixture was stirred at room temperature using an emulsion method. The sol was prepared at a temperature of 15°C and a pH of 1.5 by mixing with an overhead mixer at 500 rpm for 10 minutes. 1000 g of the sol was mixed with mineral oil (370 g) and a surfactant (sorbitan monooleate, 25 g). The emulsion was prepared by mixing continuously at a speed of 1500 rpm for 30 minutes with an overhead mixer. The pH was adjusted to 3.5 by adding ammonium hydroxide to the emulsion to control the gelation process. The temperature was then raised to 70°C and mixed at 70°C for 1 hour. 2000 g of 10 wt % sulfuric acid was then added to demulsify the mixture at 70°C at 250 rpm for 30 minutes. After demulsification, the mixture was cooled to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected and the silica particles were filtered out from the aqueous phase. The silica particles were repeatedly washed with 1500 g of 50°C water by re-slurrying the particles in water. The process was repeated three times. Then, the pore volume was controlled by following the alternative aging step (106a). The particles were redispersed in water at a pH of 3, and then ammonia was added to adjust the pH to 7.6 at 70°C for aging. After aging for 1 hour, the particles were separated and washed with water at pH, and then the particles were collected after filtration. The particles were then dried in an oven at 130°C for 10 hours. The resulting particles were spherical porous silica with a D50 particle size of 3.8 μm and a span of 0.9. The BET surface area of the resulting particles was 526 m 2 / g, pore volume 2.1ml / g, average pore diameter about Figure 7 An image of the particles is shown. The average aspect ratio was 1.03. The properties of the resulting silica particles are summarized in Table 1 below.
[0106] Example 7
[0107] The porous silica material was obtained using an emulsion method. First, sodium silicate and acid were reacted to prepare a sol, and then the sol was added to oil and a surfactant to generate an emulsion. The sol was prepared by adding 2233 g of sodium silicate (14%) to an acid (700 g, 25 wt % sulfuric acid) at a flow rate of 150 ml / min and mixing at 500 rpm for 10 minutes at a controlled temperature (≤25°C) and pH (≤1.5). 2000 g of the sol was mixed with mineral oil (850 g) and a surfactant (sorbitan monooleate, 50 g). By using The emulsion was prepared by mixing continuously at 1200 rpm for 15 minutes with an overhead mixer. The pH of the emulsion was adjusted to 3.5 by adding ammonium hydroxide to the emulsion to enhance gelation. The emulsion was heated to 70°C and then mixed at 250 rpm for 1 hour. After the reaction, 3000 g of 10 wt % sulfuric acid was added to the emulsion and mixed for 30 minutes at 80°C for 2 hours to break the emulsion. The mixture was placed for 30 minutes to separate the oil and surfactant from the resulting silica particles. The mixture was then filtered to separate the oil and surfactant from the silica particles. The silica particles were then washed three times with 1500 g of water. An alternative aging step (106a) was performed to control the pore volume. The particles were redispersed in water at a pH of 3, and then ammonia was added to adjust the pH to 7-8 at 70°C for aging. After aging, the particles were separated and redispersed at pH 4, and then the particles were collected after filtration. The wet particles were dried in an oven at 130°C for 10 hours. The resulting particles had a D50 particle size of 6.7 μm and a span of 1.4. The average BET surface area of the resulting particles was 652 m 2 / g, the average pore volume is 1.2ml / g, and the average pore diameter is about Figure 8 An image of the particles is shown. The average aspect ratio was 1.07. The properties of the resulting silica particles are summarized in Table 1 below.
[0108] Example 8
[0109] The porous silica material was obtained using an emulsion method. First, sodium silicate and acid were reacted to prepare a sol, and then the sol was added to oil and a surfactant to generate an emulsion. The sol was prepared by adding 3086 g of sodium silicate (14%) to an acid (700 g, 25 wt % sulfuric acid) at a flow rate of 100 ml / min and mixing at 500 rpm for 10 minutes at a controlled temperature (≤25°C) and pH (≤1.5). 2000 g of the sol was mixed with mineral oil (900 g) and a surfactant (sorbitan monooleate, 50 g). By using The emulsion was prepared by mixing continuously at 1000 rpm for 30 minutes with an overhead mixer. The pH of the emulsion was adjusted to 3 by adding ammonium hydroxide to the emulsion to enhance gelation. The emulsion was heated to 70°C and then mixed at 250 rpm for 1 hour. After the reaction, 3000 g of 10 wt % sulfuric acid was added to the emulsion and mixed for 30 minutes at 80°C for 2 hours to break the emulsion. The mixture was left for 30 minutes to separate the oil and surfactant from the resulting silica particles. The mixture was then filtered to separate the oil and surfactant from the silica particles. The silica particles were then washed three times with 1500 g of water. An alternative aging step (106a) was performed to control the pore volume. The particles were redispersed in water at a pH of 3, and then ammonia was added to adjust the pH to 7-8 at 70°C for aging. After aging, the particles were separated and redispersed at pH 4, and then the particles were collected after filtration. The wet particles were dried in an oven at 130°C for 10 hours. The resulting particles had a D50 particle size of 38 μm and a span of 1.7. The average BET surface area of the resulting particles was 549 m 2 / g, the average pore volume is 1.0ml / g, and the average pore diameter is about Fig. 9 An image of the particles is shown. The average aspect ratio was 1.1. The properties of the resulting silica particles are summarized in Table 1 below.
[0110] Example 9
[0111] The porous silica material was obtained using an emulsion method. First, sodium silicate and acid were reacted to prepare a sol, and then the sol was added to oil and a surfactant to generate an emulsion. The sol was prepared by adding 2411 g of sodium silicate (14%) to an acid (700 g, 25 wt % sulfuric acid) at a flow rate of 100 ml / min and mixing at 500 rpm for 10 minutes at a controlled temperature (≤25°C) and pH (≤1.5). 2000 g of the sol was mixed with mineral oil (750 g) and a surfactant (sorbitan monooleate, 50 g). By using The emulsion was prepared by continuous mixing at 1200 rpm with an overhead mixer for 30 minutes. The emulsion was heated to 70°C and then mixed at 250 rpm for 1 hour. After the reaction, 3000 g of 10 wt % sulfuric acid was then added to demulsify the mixture at 80°C at 250 rpm for 2 hours. After demulsification, the mixture was cooled to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected, and the silica particles were filtered out from the aqueous phase. The silica particles were repeatedly washed with 50°C water by re-slurrying the particles in 1500 g of water. This process was repeated three times. Then, the particles were subsequently dried in an oven at 130°C for 10 hours. The resulting particles were spherical porous silica with a D50 particle size of 30 μm and a span of 1.7. The BET surface area of the resulting particles was 750 m 2 / g, pore volume is 0.5ml / g, and average pore diameter is about Fig.10 An image of the particles is shown. The average aspect ratio was 1.11. The properties of the resulting silica particles are summarized in Table 1 below.
[0112] Table 1 summarizes the properties of the silica particles produced in Examples 1-9.
[0113] Table 1
[0114] Certain embodiments
[0115] Embodiment 1. A method for forming porous spherical silica, the method comprising:
[0116] a. mixing an alkali metal silicate with an inorganic acid at a pH and temperature sufficient to form a silica sol,
[0117] b. mixing the silica sol with oil and a surfactant to form an emulsion,
[0118] c. adding an alkaline solution to the emulsion at a time and temperature sufficient to form a gel,
[0119] d. adding a demulsifier and heating at a temperature sufficient to separate the porous spherical silica particles from the oil,
[0120] e. washing and optionally aging the particles, and
[0121] f. Drying the porous spherical silica particles.
[0122] Embodiment 2. The method of embodiment 1, wherein the alkali metal silicate is sodium silicate.
[0123] Embodiment 3. The method according to Embodiment 1 or Embodiment 2, wherein the inorganic acid is sulfuric acid or hydrochloric acid.
[0124] Embodiment 4. The method of any one of Embodiments 1-3, wherein the oil comprises mineral oil.
[0125] Embodiment 5. The method of any one of Embodiments 1-4, wherein the surfactant comprises a nonionic surfactant.
[0126] Embodiment 6. The method of embodiment 5, wherein the surfactant comprises a sorbitan ester.
[0127] Embodiment 7. The method of embodiment 6, wherein the surfactant comprises sorbitan oleate.
[0128] Embodiment 8. The method of any one of Embodiments 1-7, wherein the alkaline solution comprises ammonium hydroxide.
[0129] Embodiment 9. The method of any one of embodiments 1-8, wherein the emulsion is maintained at a temperature of about 40°C to about 90°C for about 0.25 hour to about 2 hours prior to adding the demulsifier.
[0130] Embodiment 10. The method of any one of embodiments 1-9, wherein the alkaline solution is added until the pH reaches a level of about 5 to about 10.
[0131] Embodiment 11. The method according to embodiment 10, wherein the alkaline solution is added until the pH reaches a level of about 6 to about 9.
[0132] Embodiment 12. The method of any one of Embodiments 1-11, wherein the silica sol is formed at a temperature below 25°C.
[0133] Embodiment 13. The method of any one of Embodiments 1-12, wherein the particles are aged after washing and before drying.
[0134] Embodiment 14. The method of embodiment 13, wherein the particles are aged at a pH of about 7 to about 9 at a temperature of about 60°C to about 90°C for a period of time of about 1 hour to about 4 hours.
[0135] Embodiment 15. The method of any one of embodiments 1-14, wherein the emulsion is formed by mixing the silica sol with a mixture comprising an oil and a surfactant.
[0136] Embodiment 16. The method of embodiment 15, wherein the concentration of the surfactant in the surfactant / oil mixture ranges from about 3% to about 25% by weight of the mixture.
[0137] Embodiment 17. The method of embodiment 15, wherein the concentration of the surfactant in the surfactant / oil mixture ranges from about 4% to about 15% by weight of the mixture.
[0138] Embodiment 18. The method of embodiment 15, wherein the concentration of the surfactant in the surfactant / oil mixture ranges from about 5% to about 8% by weight of the mixture.
[0139] Embodiment 19. The method of any one of embodiments 1-18, wherein the ratio of silica sol to surfactant / oil mixture ranges from about 1:5 to about 5:1.
[0140] Embodiment 20. The method of any one of embodiments 1-19, wherein the ratio of silica sol to surfactant / oil mixture ranges from about 1:3 to about 4:1.
[0141] Embodiment 21. The method of any one of embodiments 1-20, wherein the ratio of silica sol to surfactant / oil mixture ranges from about 1:2 to about 2:1.
[0142] Embodiment 22. The method of any one of Embodiments 1-21, wherein the demulsifier comprises an inorganic acid.
[0143] Embodiment 23. A silica material formed by the method of any one of Embodiments 1-22, the silica material comprising:
[0144] A plurality of single-grain silica gel particles, each particle comprising an amorphous network, the particles having an average aspect ratio of about 1.2 or less, a pore volume of about 0.5 cc / g to about 2.5 cc / g, and a surface area of about 300 m 2 / g to about 800m 2 / g; median particle size is about 3 μm to about 40 μm.
[0145] Embodiment 24. A silicon dioxide material formed by the method according to Embodiments 1-22, the silicon dioxide material comprising:
[0146] A plurality of single-grain silica gel particles, each particle comprising an amorphous network, the particles having an average aspect ratio of about 1.2 or less, a pore volume of about 0.8 cc / g to about 2.0 cc / g, and a surface area of about 400 m 2 / g to about 700m 2 / g; median particle size is about 8 μm to about 40 μm.
[0147] Embodiment 25. The silica material of Embodiment 23 or Embodiment 24, wherein the silica particles have a span of about 2.0 or less.
[0148] Embodiment 26. The silica material of Embodiment 23 or Embodiment 24, wherein the silica particles have an average pore size of about 30 angstroms to about 250 angstroms.
Claims
1. A method for forming porous spherical silica, the method comprising: a. mixing an alkali metal silicate with an inorganic acid at a pH and temperature sufficient to form a silica sol, b. mixing the silica sol with oil and a surfactant to form an emulsion, c. adding an alkaline solution to the emulsion at a time and temperature sufficient to form a gel, d. adding a demulsifier and heating at a temperature sufficient to separate the porous spherical silica particles from the oil, e. washing and optionally aging the particles, and f. Drying the porous spherical silica particles.
2. The method according to claim 1, wherein the alkali metal silicate is sodium silicate.
3. The method according to claim 1 or claim 2, wherein the inorganic acid is sulfuric acid or hydrochloric acid.
4. The method of any one of claims 1-3, wherein the oil comprises mineral oil.
5. The method of any one of claims 1-4, wherein the surfactant comprises a nonionic surfactant.
6. The method of claim 5, wherein the surfactant comprises a sorbitan ester.
7. The method of claim 6, wherein the surfactant comprises sorbitan oleate.
8. The method of any one of claims 1-7, wherein the alkaline solution comprises ammonium hydroxide.
9. The method of any one of claims 1-8, wherein the emulsion is maintained at a temperature of about 40°C to about 90°C for about 0.25 hour to about 2 hours prior to adding the demulsifier.
10. The method of any one of claims 1-9, wherein the alkaline solution is added until the pH reaches a level of about 5 to about 10.
11. The method of claim 10, wherein the alkaline solution is added until the pH reaches a level of about 6 to about 9.
12. The method of any one of claims 1-11, wherein the silica sol is formed at a temperature below 25°C.
13. A method according to any one of claims 1 to 12, wherein after washing and before drying the particles are aged.
14. The method of claim 13, wherein the particles are aged at a pH of about 7 to about 9 at a temperature of about 60°C to about 90°C for a period of about 1 hour to about 4 hours.
15. The method of any one of claims 1 to 14, wherein the emulsion is formed by mixing a silica sol with a mixture comprising an oil and a surfactant.
16. The method of claim 15, wherein the concentration of the surfactant in the surfactant / oil mixture ranges from about 3% to about 25% by weight of the mixture.
17. The method of claim 15, wherein the concentration of the surfactant in the surfactant / oil mixture ranges from about 4% to about 15% by weight of the mixture.
18. The method of claim 15, wherein the concentration of the surfactant in the surfactant / oil mixture ranges from about 5% to about 8% by weight of the mixture.
19. The method of any one of claims 1-18, wherein the ratio of silica sol to surfactant / oil mixture ranges from about 1:5 to about 5:
1.
20. The method of any one of claims 1-19, wherein the ratio of silica sol to surfactant / oil mixture ranges from about 1:3 to about 4:
1.
21. The method of any one of claims 1-20, wherein the ratio of silica sol to surfactant / oil mixture ranges from about 1:2 to about 2:
1.
22. The method of any one of claims 1-21, wherein the demulsifier comprises an inorganic acid.
23. A silicon dioxide material formed by the method of any one of claims 1-22, the silicon dioxide material comprising: A plurality of single-grain silica gel particles, each particle comprising an amorphous network, the particles having an average aspect ratio of about 1.2 or less, a pore volume of about 0.5 cc / g to about 2.5 cc / g, and a surface area of about 300 m 2 / g to about 800m 2 / g; median particle size is about 3 μm to about 40 μm.
24. A silicon dioxide material formed by the method of any one of claims 1-22, the silicon dioxide material comprising: A plurality of single-grain silica gel particles, each particle comprising an amorphous network, the particles having an average aspect ratio of about 1.2 or less, a pore volume of about 0.8 cc / g to about 2.0 cc / g, and a surface area of about 400 m 2 / g to about 700m 2 / g; median particle size is about 8 μm to about 40 μm.
25. A silica material according to claim 23 or claim 24, wherein the silica particles have a span of about 2.0 or less.
26. The silica material of claim 23 or claim 24, wherein the silica particles have an average pore size of about 30 angstroms to about 250 angstroms.
